Verification and Validation exercises for the flow around the KVLCC2 tanker at model and full-scale Reynolds numbers. (1st January 2017) - Pereira, F.S.; Eça, L.; Vaz, G.
Abstract: This paper presents the quantification of numerical and modelling errors for the solution of the flow around the KVLCC2 tanker at model-scale Reynolds number. Numerical errors are also quantified for full-scale Reynolds number simulations to address the numerical accuracy of the prediction of scale-effects. The calculations are performed with the solver ReFRESCO using fourteen distinct Reynolds-Averaged Navier-Stokes (RANS) equations models. The quantities of interest for the Validation exercises at model-scale are the resistance coefficient and the velocity and turbulence kinetic energy fields at the propeller plane. Modelling errors are estimated using the ASME V&V20 procedure which requires numerical and experimental data with their respective uncertainties. Numerical uncertainties are dominated by the contribution of the discretization error, which is determined by grid refinement studies. Scale-effects are also assessed for the wake-fraction and form-factor. The outcome shows that quantifying modelling errors is not a trivial exercise that depends on the quality and details of simulations and experiments. Nonetheless, it is also evident that a quantitative evaluation of modelling errors is more reliable than traditional graphical comparisons of simulations and experiments. Full-scale results show scale-effects larger than numerical uncertainties that are illustrated for the form-factor and wake-fraction. Highlights: Comparison of 14 turbulence models for a realistic ship flow. Assessment of the iterative convergence effect on the simulation accuracy. Robust implementation of models for Re=4.6E6 (model) and Re=2.0E9 (full-scale). Numerical and modelling errors quantification for local and integral quantities. Assessment of Scale-Effects.